Investigate Performance of IEEE 802.11b Using OPNET - Jasim, Hayder M. (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: In recent years, the research community interest has increased about wireless ad hoc networks. IEEE 802.11b standard is one of the wireless network standards which is used in such network these groups’ standards. The IEEE 802.11b standard defines the protocol and proper interconnections of data communication tools wireless local area network (LAN). It includes the physical and media access control (MAC) layers of the ISO seven-layer network model. Therefore, investigating its performance with different ad hoc network configurations is necessary. Routing protocols like AODV, DSR, TORA and OLSR are famous studies that discourse the performance evaluation of routing protocols via different evaluation methods. Various methods and simulation environments grant different outcomes. Thus, there is a need to broaden the spectrum to account for effects not taken into consideration in a particular environment. There is a need to expand the spectrum to take into consideration the effects of file size, numbers of nodes and mobility that were neglected in a specific environment. During the time of the thesis, the performance of AODV, ad hoc routing protocol in OPNET was evaluated using several scenarios. Effectiveness of this approach with 802.11b standard in various wireless ad hoc network configurations was investigated. The simulation results were analyzed and compared. In our simulation work, FTP traffic is used between a client and FTP server through other entire nodes with AODV protocol and 802.11b wireless standard. Our simulation results would also represent a situation where a MANET node can receive traffic from another node in the network. Furthermore, the nodes are randomly scattered in the network to provide the possibility of multi hop routes from the client to the server. Keywords: Mobile Wireless ad Hoc Networks, Routing Protocol, Performance Evaluation, OPNIT simulator, AODV. ………………………………………………………………………………………………………………………… ÖZ:Son yıllarda, araştırma topluluğunun ilgisi kablosuz özele amaca yönelik (ad hoc) ağlar hakkında artmıştır. IEEE 802.11b standardı, bu ağlarda kullanılan kablosuz ağ standartlarından biridir. IEEE 802.11b standardı very iletişim için gerekli kablosuz yerel alan ağında (LAN) protokolü ve uygun bağlantıları tanımlar. Standart, yedi katmanlı ISO ağ modelinde fiziksel ve ortam erişim denetimi (MAC) katmanlarını içerir. Bu nedenle, farklı ad hoc ağ yapılandırmalarında bu standartın performans araştırmak gereklidir. AODV, DSR, TORA ve OLSR gibi yönlendirme protokollerinin farklı değerlendirme yöntemleri ile yönlendirme protokolleri performansın değerlendirme de kullanılan ünlü çalışmalardır. Çeşitli yönlendirme yöntemleri ve simülasyon ortamları farklı sonuçlar vermek. Bu yüzden performans ölçülerinde belirli bir ortam dikkate alınmak yerine farklı ortamlarda göz önünde bulundurmak gerekir. Farklı ortamlarda, dosya boyutu, düğüm sayısı ve düğümlerin hareketliliğinin etkilerini incelemeye gerek vardır. Bu tezde bilinen bir yönlerdirme protokolü olan AODVi, OPNET simulatörü kullanılarak farklı ağ senaryolarında değerlendirilmiştir. Çeşitli kablosuz ad hoc ağ yapılandırmalarında 802.11b standardının etkinliği araştırılmıştır. Elde edilen simülasyon sonuçları analiz edilip karşılaştırılmıştır. Simülasyon çalışmalarında, AODV protokolü ve 802.11b kablosuz standart kullanarak işlemci ve sonucu düğümler arasında FTP trafiği oluşturulmuştur. Ayrıca simülasyonlarda kablosusun bir ad hoc güğümünün başka bir düğümün erişim alanında olmadığı durumlar da göz önüne alınmıştır. Ayrıca, düğümler ağda rasgele yerleştirilerde istemciden sunucuya çok hop yollarınoluşması sağlanmıştır. Anahtar Kelimeler: Mobil Kablosuz Özel Amaca Yönekli Ağlar, Yönlendirme Protokolü, Performans Değerlendirme, OPNET simülatörü, AODV Yönlerdirme Protokolü.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2013. Supervisor: Assist. Prof. Dr. Gürcü Öz.
Keywords: Computer Engineering; Wireless communication systems; Mobile Wireless ad Hoc Networks, Routing Protocol, Performance Evaluation, OPNIT Simulator, AODV